Perlaksanaan Customary Tenure Enactment (CTE) Zaman Kolonial dan Kesannya ke Atas Pentadbiran Tanah Adat di Negeri Sembilan (1921–1940) - Azwan Syah Idris,; Nordin Hussin,; Ishak Yussof, (Kajian Malaysia, 2015)
This study attempts to unravel the implementation of Customary Tenure Enactment (CTE) in Negeri Sembilan which is still practicing the Adat Perpatih. The colonisation of Negeri Sembilan by the British has resulted in changes to the practices, in line with the economic situation at the time and their focus on land management affairs. Customary land was an important asset for the adat of the community as a continuation of their economic strength. Realising this, the year of 1909 was the beginning of the establishment of CTE especially for those customary lands that had been enacted by the British based on the land law of Adat Perpatih. CTE was enacted to ensure customary lands were not transferrable to other individuals particularly the foreigners. In this respect, each customary land would be marked as customary land in the land grant to indicate that the land has been permanently held and cannot be sold. Notwithstanding this however, if the customary land tag was to be annulled, that piece of land would then be transferrable. This has raised concerns on the effectiveness of the law to protect the customary lands as well as on the understanding of the adat community of the CTE. The objective of this study is to examine changes and effect of CTE on adat community. The findings of the study showed that there have been changes that had impacted the sustainability of customary lands. Under the British administration from the early 1930's until the early 1940's, changes had been seen to occur in the mindset of the adat community with the occurrences of a number of customary lands annulments to enable the selling of customary lands. This has definitely run contrary to the original intention of CTE. The establishment of CTE to protect customary lands has now become a "facility" for the adat community to sell their land. The weaknesses of CTE have not been able to protect land and adat and the economic changes have also impacted the community's mindsets. Kajian ini mengupas perlaksanaan Customary Tenure Enactment (CTE) di Negeri Sembilan yang mengamalkan Adat Perpatih. Penjajahan British ke Negeri Sembilan telah memberi perubahan seiring dengan keadaan ekonomi ketika itu dan antara tumpuan utama mereka ialah hal ehwal pengurusan tanah. Tanah adat merupakan aset penting bagi masyarakat adat yang menjadi kesinambungan kekuatan komuniti mereka. Menyedari hal ini, tahun 1909 menjadi permulaan kepada kewujudan CTE khusus bagi tanah adat yang digubal oleh British berdasarkan undang-undang tanah Adat Perpatih. CTE digubal bagi memastikan tanah adat tidak boleh dipindah milik kepada individu lain terutama bangsa asing. Setiap tanah adat akan ditanda customary land di dalam gerannya bagi menunjukkan tanah itu menjadi hak milik tetap dan tidak boleh dijual. Namun, jika customary land itu dibatalkan, tanah ini bebas ditukar milik. Hal ini menimbulkan persoalan iaitu sejauh manakah undang-undang ini berjaya melindungi tanah adat dan kefahaman masyarakat adat terhadap CTE. Objektif kajian ini bagi meneliti perubahan dan kesan CTE kepada masyarakat adat. Hasil kajian mendapati telah berlaku perubahan dan kesan kepada tanah adat. Memasuki tahun 1930-an hingga awal 1940-an pentadbiran British, perubahan mulai kelihatan kepada pemikiran masyarakat adat dengan terdapatnya kes-kes membatalkan tanda customary land bagi memudahkan urusan menjual tanah adat yang jelas tidak tepat berdasarkan matlamat asal CTE. Kewujudan CTE bagi melindungi tanah adat telah bertukar menjadi satu kemudahan bagi masyarakat adat menjual tanah mereka. Kelemahan yang terdapat dalam CTE tidak mampu melindungi tanah adat dan perubahan ekonomi telah mendatangkan kesan kepada pemikiran masyarakatnya.